2021
DOI: 10.1590/0037-8682-0254-2021
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate form of Chagas disease: historical, conceptual, clinical, and prognostic aspects

Abstract: Chagas disease (CD) remains a serious endemic disease in Latin America and a major public health problem. Because of globalization, the disease has spread to non-endemic areas in the northern hemisphere. In the chronic phase of the disease, most patients present with the indeterminate form (IF), characterized by positive serology for Trypanosoma cruzi, absence of clinical findings, and normal findings in electrocardiogram (ECG). IF was not recognized as a clinical entity until decades after the discovery of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Nevertheless, recent studies have revealed that myocardial involvement in CD is not restricted to patients with CCM, as patients in the IF of the disease have also exhibited pathological findings such as myocyte degeneration and ongoing fibrosis [ 51 , 52 ]. The IF of CD is defined as the presence of a positive anti- T. cruzi serology (based on two different assays) along with the absence of symptoms or physical signs of disease, a normal electrocardiogram, and normal chest and gastrointestinal radiographic studies [ 1 , 9 , 53 ]. However, these criteria were defined almost 40 years ago, relying on relatively simple measures and heart and myocardial function assessments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, recent studies have revealed that myocardial involvement in CD is not restricted to patients with CCM, as patients in the IF of the disease have also exhibited pathological findings such as myocyte degeneration and ongoing fibrosis [ 51 , 52 ]. The IF of CD is defined as the presence of a positive anti- T. cruzi serology (based on two different assays) along with the absence of symptoms or physical signs of disease, a normal electrocardiogram, and normal chest and gastrointestinal radiographic studies [ 1 , 9 , 53 ]. However, these criteria were defined almost 40 years ago, relying on relatively simple measures and heart and myocardial function assessments.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the concept of “indeterminate form” has been widely debated, as several studies have reported anatomical and functional myocardial derangements in patients with this form of CD [ 54 ]. The reported functional alterations include anomalies in left ventricle contractility, atrioventricular conduction disorders, alterations in the systolic function of the right ventricle, and even LV segmental wall motion abnormalities [ 9 , 22 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the article by Hasslocher-Moreno and colleagues about the indeterminate form of Chagas Disease (CD) 1 .…”
Section: Dear Editormentioning
confidence: 99%
“…More importantly, from a pathophysiological point of view, it remains unclear why some patients, after the acute phase of CD, manifest cardiac or gastrointestinal symptoms (or even a combination of them), while the majority remain in the indeterminate form, with a life expectancy similar to that of uninfected participants 2,3 . Factors related to Trypanosoma cruzi infection in areas with sustained vector transmission, male sex, parasite load, genetic aspects of the host, nutritional status, comorbidities, and the social context and quality of life of patients with CD are involved 1 . In addition, we believe that an imbalance between some cell actors in the host's immune system and the parasite is also involved.…”
Section: Dear Editormentioning
confidence: 99%